Integrasi Teknologi Penginderaan Jauh dan Prinsip Maqashid Syariah dalam Pemantauan Polusi Udara di DKI Jakarta - Anandari, Anatansyah Ayomi (Kaunia: Integration and Interconnection Islam and Science Journal, 2025)
The increasing intensity of air pollution in the DKI Jakarta area has become an urgent environmental issue, with significant impacts on public health and the sustainability of urban ecosystems. This study aims to integrate remote sensing technology and the principles of Maqashid Syariah in monitoring and analyzing air quality, in order to present an approach that is not only technical but also ethical and spiritual in environmental management. This research employs a descriptive qualitative method through a case study design, utilizing spatial data from Sentinel-5P satellite imagery to map the distribution of pollutants such as NO₂ and SO₂, while examining this data through the lens of the five main principles of Maqashid Syariah (hifz al-din, hifz al-nafs, hifz al-‘aql, hifz al-nasl, and hifz al-mal). The findings indicate that the areas with the highest levels of pollution overlap with violations of the core objectives of Islamic law, particularly the protection of life and intellect. This study emphasizes the urgency of integrating science and Islamic values as a conceptual and practical foundation for developing public policies that are ecologically just and spiritually grounded.